1991
DOI: 10.1161/01.atv.11.5.1156
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A reductase induce reductase accumulation and altered lamellar bodies in rat forestomach keratinocytes.

Abstract: Lovastatin, an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and a potent hypocholesterolemic agent, induces a hyperplastic thickening of the rat forestomach mucosa after oral administration of its active form, a hydroxyacid. We studied the effects of lovastatin on the intracellular accumulation of HMG-CoA reductase immunostaining and the accompanying morphological changes in rat forestomach keratinocytes by immunofluorescence microscopy and transmission electron microscopy (TEM). Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…This change has the appearance of local irritation but is not produced by structurally similar but biochemically inactive isomers of active agents suggesting that this effect is mediated through inhibition of HMG-CoA reductase . Induction of HMG-CoA reductase and corresponding proliferation of smooth endoplasmic reticulum in forestomach keratinocytes (similar to what was observed in rat hepatocytes) was demonstrated in rats receiving lovastatin or its hydroxyacid form (Singer et al, 1991). While these changes seem to be mechanism-based, they appear to require a very high local concentration of active drug.…”
Section: Additional Findings In Animals That Represent Exaggerated Bisupporting
confidence: 73%
See 1 more Smart Citation
“…This change has the appearance of local irritation but is not produced by structurally similar but biochemically inactive isomers of active agents suggesting that this effect is mediated through inhibition of HMG-CoA reductase . Induction of HMG-CoA reductase and corresponding proliferation of smooth endoplasmic reticulum in forestomach keratinocytes (similar to what was observed in rat hepatocytes) was demonstrated in rats receiving lovastatin or its hydroxyacid form (Singer et al, 1991). While these changes seem to be mechanism-based, they appear to require a very high local concentration of active drug.…”
Section: Additional Findings In Animals That Represent Exaggerated Bisupporting
confidence: 73%
“…A final drug-induced adverse effect that is common to statins and likely mechanism-based is hyperplasia, hyperkeratosis and submucosal edema in the squamous epithelium of the nonglandular forestomach in mice and rats (Corsini et al, 1996;MacDonald et al, 1986;Gerson et al, 1988;Singer et al, 1991;Kloss et al, 1991). Although the mechanism for this effect on this specific subpopulation of gastric epithelium in rodents is not clear, it is characterized by the proliferation of squamous epithelial cells accompanied by submucosal edema and hyperkeratosis.…”
Section: Additional Findings In Animals That Represent Exaggerated Bimentioning
confidence: 99%
“…1991). The forestomach toxicity of these agents appears to be linked to their pharmacologic mechanism of action (Singer et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of the hyperplastic response correlates with in vitvo enzyme inhibition of these compounds, and no impairment of the forestomach occurs after subcutaneous administration. The effects of lovastatin and simvastatin are accompanied with increases in HMG-CoA reductase levels within forestomach keratinocytes (Singer et al 1991). The authors hypothesize that the occurrence of rodent forestomach alterations in response to lovastatin hydroxyacid and simvastatin is dependent on the mechanism of action of these HMG-CoA reductase inhibitors.…”
mentioning
confidence: 98%
“…Detailed morphological study of the forestomach in rats treated with lovastatin suggested that it is related to the effects on the assembly of cholesterol and other lipids into the lamella bodies and intracellular lipid sheets. 224 Their tumorigenic potential in rodent bioassays does not seem to relate to the degree of hyperplasia in short-term studies. 204 Moreover, the development of hyperplasia depends on local high concentrations of drug because when administered by non-oral routes, hyperplasia does not occur.…”
Section: Human Relevance Of Proliferative Lesions Induced By Drugs Inmentioning
confidence: 99%